Analisis Perbedaan Preferensi Konsumen dalam Mengkonsumsi Beras Kampung dan Beras Pasar di Wilayah Desa Andeng Kecamatan Sengah Temila - Salirta, Dela; Beni, Sabinus; Atlantika, Yeremia Niaga; Usman, Usman (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research was conducted with the aim of observing and finding out the extent of consumers’ preferences for consuming village rice. This research was carried out using qualitative methods through data collection by conducting observations and interviews. The results of this research are that village rice has several attribute elements such as price, shape of rice, taste, aroma, color and packaging size. These product attributes are one way to develop products and services that have been used by business actors. This product attribute can help consumers to differentiate village rice products from market rice because both have different attributes so that with these product attributes business actors can see consumer preferences in consuming village rice. Consumer preferences in the Andeng village area, Sengah Temila sub-district, Landak district can be seen from how often consumers buy or consume village rice sold by business actors. In terms of consumer interests and tastes, many consumers prefer to buy village rice rather than buy rice in the market because the price of village rice is cheaper than the price of market rice